BROMALITES FROM THE SOOM SHALE LAGERSTäTTE (UPPER ORDOVICIAN) OF SOUTH AFRICA: PALAEOECOLOGICAL AND PALAEOBIOLOGICAL IMPLICATIONS - Aldridge R.J.; Gabbott S.E.; Siveter L.J.; Theron J.N. (My University, 2006)
Bromalites from the Soom Shale are allocated to five main categories on the basis of shape, content and internal structure: those containing broken conodont elements; those containing brachiopod fragments; corrugated/spiral forms; coiled coprolites and wrinkled coprolites. It is impossible to allocate specific bromalites to the organisms that formed them, but the occurrence of crushed discinoid valves in several specimens demonstrates that an effective durophagous predator was present in the Soom Shale community. The presence of fragmented elements of conodonts in other specimens provides direct evidence of tiering within the predatory trophic level in the Soom Shale. Conodonts, other agnathan vertebrates, orthoconic cephalopods and eurypterids are all possible contenders for producing most of the bromalites recorded, but there may have been unrecorded large predators in the community. © 2006 The Palaeontological Association.
Keywords: BROMALITES; COPROLITES; ORDOVICIAN; PALAEOBIOLOGY; PALAEOECOLOGY; SOOM SHALE; SOUTH AFRICA; Paleozoic::Ordovician; Палеозой::Ордовикская